Sello sa ngwana (A child's lament) - Benelzane, Phukoane (Open Mic: A Creative Writing Journal, 2024)
Oh! How sweet and loud the birds sing on this gloomy day!Their songs break through the fog of grief.My heart beats slowly and softly as the muffled drum.Oh! how I long to shout and praise the Lord!But my chest turns to heavy stone,And I remember the fluttering leavings of May,When the coldness of Winter crept into our home,And began to seep deep into your bones. In my heart I am left with the ruinsOf the memories we created.I hold on dimly to the visionsOf the day I saw you last.But I as close my eyes,I see the cancer gradually eat awayThe soft tissue of your skin.And in my soul there still lies,A yearning to call for the Lord!In your final days you became even more beautiful.The stars were written in the sparkle of your eyes,As your heavenly wings began to grow.But I was never ready for your flying away!When you broke away through the winter snow. Years later I stand before your grave and weep,Like a newborn child – drawing his first breath.You are a servant of the Lord before you are my mother,And I know you rest well with our Heavenly father!